Comparative proteomics reveals the mechanism of cyclosporine production and mycelial growth in Tolypocladium inflatum affected by different carbon sources - Wang, Junqi; Liu, Meijie; Mao, Chengzhi; Li, Sizhu; Zhou, Jiabao; Fan, Yaqin; Guo, Lizhong; Yu, Hao; Yang, Xiuqing (Frontiers in Microbiology, 2023)
Cyclosporine A (CsA) is a secondary cyclopeptide metabolite produced by Tolypocladium inflatum that is widely used clinically as an immunosuppressant. CsA production and mycelial growth differed when T. inflatum was cultured in different carbon source media. During early fermentation, CsA was preferred to be produced in fructose medium, while the mycelium preferred to accumulate in sucrose medium. On the sixth day, the difference was most pronounced. In this study, high-throughput comparative proteomics methods were applied to analyze differences in protein expression of mycelial samples on day 6, revealing the proteins and mechanisms that positively regulate CsA production related to carbon metabolism. The differences included small molecule acid metabolism, lipid metabolism, organic catabolism, exocrine secretion, CsA substrate Bmt synthesis, and transcriptional regulation processes.The proteins involved in the regulation of mycelial growth related to carbon metabolism were also revealed and were associated with waste reoxidation processes or coenzyme metabolism, small molecule synthesis or metabolism, the stress response, genetic information or epigenetic changes, cell component assembly, cell wall integrity, membrane metabolism, vesicle transport, intramembrane localization, and the regulation of filamentous growth. This study provides a reliable reference for CsA production from high-efficiency fermentation. This study provides key information for obtaining more CsA high-yielding strains through metabolic engineering strategies.